Rubella immunisation and contraception—a case for re-examining the policy of the Department of Health and Social Security - Rose, A. J. (1976)
Now that immunisation against rubella is available, it would at first sight seem reasonable to identify all potential mothers susceptible to this disease and immunise them. Preliminary screening, however, carried out in order to restrict vaccination to seronegative subjects, not only serves no useful purpose, but is counter-productive.